Sex Manipulation Technologies Progress in Livestock: A Review - Xie, Yanshe; Xu, Zhiqian; Wu, Zhenfang; Hong, Linjun (Frontiers in Veterinary Science, 2020)
Sex determination technology allows predetermination of the sex of animal offspring by manipulating the normal reproductive process. In livestock production, the difference in type and gender can translate into significant economic benefits, including alleviation of severe food shortages. In livestock however, the commercial application of sex determination technology is currently available for cattle only. In this review, we described the brief history of sex determination, and the research progresses of common methods used in sex determination thus far. Information presented in this review can inform future studies on expanding the scope and use of sex determination technology in livestock.